Eliminación de árboles indeseables mediante agentes químicos - Mayo Menéndez, E. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A review is made of the literature on aboricides. Chemicals have the advantage over tree felling that there is no damage to surrounding trees and there is no sudden break in the canopy. Better effects of aboricides are found when applied by girdling. Sodium arsenite is very efficient but is toxic. Hormone seem a good substitute to arsenicals because its lack of toxicity. Best vehicle for hormones is Diesel oil due to its penetration power and for having itself a direct weak aboricidal effect.